Apresentação pélvica - Construção de um modelo preditivo da via de parto - Trocado,Vera (2019)
Overview and Aims: The decision of the route of delivery in a breech presentation is one of the most controversial topics in contemporary obstetrics. The aim of this study is to develop a predictive model for vaginal breech delivery (VBD). Study Design, Population and Methods: It was performed an observational, retrospective, descriptive study based on the review of clinical records of pregnant woman with singleton gestations in breech presentation at term, with delivery between 2005 and 2015, in Hospital de Braga and Unidade Local de Saúde do Alto Minho. Potential predictors of VBD were analyzed by bivariate analysis and binary logistic regression. Results: There were included 92 VBD and 167 cesareans. The final model includes 6 variables: Maternal age, number of previous deliveries, percentile of estimated fetus weight, weight of the heaviest previous newborn, Bishops index and fetal gender. The area under the curve was 0,83, corresponding to a good discriminative ability. A probability equal to or greater than 50.3% may be an adjunct to the decision of the delivery route. Conclusions: A predictive model with good discriminative capacity was developed that can be useful helping the decision of the route of delivery in pregnant woman with singleton gestations in breech presentation at term.